Technology Name and Celebrity Endorsement Effects of Autonomous Vehicle Promotional Messages: Mechanisms and Moderators. Issue 1 (February 2019) - Myrick, Jessica Gall; Ahern, Lee; Shao, Ruosi; Conlin, Jeff
Autonomous vehicles represent an emerging technology with the potential to radically transform everyday life. Yet there is little understanding of how promotional tactics—easy-to-grasp technology labels or pairing the technology with well-known celebrities—influence public perceptions of risk, benefits, and intentions. Therefore, we experimentally tested ( N = 721) the effects of technology name and celebrity presence on emotional, cognitive, and behavioral responses to promotional messages. Moreover, we examined how individual differences and attention to news about autonomous vehicles can moderate responses. Results of this exploratory study revealed the importance of affective and cognitive mediators and audience-related moderators in shaping responses.